(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The crescent moon, a symbol with deep significance in Islamic culture and notable recognition in Western contexts, represents a complex interaction of meanings that bridge cultural divides. This article investigates the historical development of the crescent moon, tracing its origins from ancient civilizations to its important role in Islamic society, where it serves as a marker of the lunar calendar and symbolizes renewal during key religious observances. In contrast, Western interpretations of the crescent often focus on themes such as femininity, creativity, and mystery. By exploring the dual meanings of the crescent moon, this article underscores its potential to act as a cultural bridge, enhancing dialogue and fostering understanding between Islamic and Western societies.